외래 의료서비스 이용 환자의 환자참여 경험이 환자만족에 미치는 영향 - 안신애(Ahn, Shinae) (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2022)
연구목적: 본 연구의 목적은 환자가 경험한 외래 의료서비스 이용 과정에서의 환자참여 경험 정도와 환자만족 현황을 파악하고 환자만족에 영향을 미치는 요인을 파악하기 위함이다. 연구방법: 본 연구는 ‘2018년 의료서비스경험조사’ 데이터를 사용하여 의원급과 병원급 의료기관의 외래 의료서비스 이용 경험이 있는 20세 이상의 성인 6,684명의 자료를 분석하였다. 환자만족에 영향을 미치는 요인은 환자 특성, 건강관련 특성, 환자참여 경험으로 분류하였으며 로지스틱 회귀분석을 통해 분석하였다. 연구결과: 대상자의 84.9%가 외래 의료서비스에 만족하는 것으로 나타났다. 외래 의료서비스를 이용하는 환자의 환자만족에는 연령, 주관적 건강수준, 환자참여 경험이 유의한 영향을 미치는 것으로 확인되었다. 결론: 환자만족에는 다양한 요인이 관련되어 있으며 이러한 요인을 고려하여 환자만족을 평가할 필요가 있다. 외래 의료서비스를 이용하는 환자의 만족을 높이려면 환자참여를 증진시키기 위한 의료정책 및 전략 수립을 통해 치료과정에서 환자가 참여할 수 있는 기회를 확대해 주는 것이 필요하다. Purpose: This study examined outpatients’ experiences of patient participation, their level of patient satisfaction, and the factors that influence their patient satisfaction with outpatient care. Methods: This cross-sectional descriptive study utilized secondary data from the 2018 Survey on the Experience with Healthcare Service conducted in South Korea. Data from 6,684 outpatients over the age of 20 years who had visited hospitals were analyzed. Patient characteristics, health-related characteristics, and their experiences of patient participation were assessed as factors related to patient satisfaction. Factors that influenced patient satisfaction with outpatient care were identified using logistic regression analysis. Results: Overall, 84.9% of the participants were satisfied with the received outpatient care. Higher patient satisfaction with outpatient care was significantly associated with middle (40-59 years) and old age (≥60 years), good self-rated health status, and experience of patient participation in patient safety activities. Conclusion: Multiple factors were related to patient satisfaction with outpatient care. These factors need to be considered when evaluating patients’ satisfaction levels. To improve satisfaction with health care use, it is essential to provide more experiences and expand their opportunities for patient participation during the care process and establish healthcare policies and strategies to enhance patient participation in patient safety. KCI Citation Count: 0